Antecedents for Creating Loyal Relationship with Retailers: A Study on the Pharmaceutical Industry of Bangladesh - Jamil , Md. Abdullah Al (Annals of Management and Organization Research, 2021)
Purpose: The study looked at a variety of factors that go into building a loyal relationship between a company and its retailers in Bangladesh's pharmaceutical industry. Research methodology: Ten (10) hypotheses were established based on the literature review. Furthermore, the convenience sampling technique was used to choose the samples. Data were collected from 50 different retailers. In addition, the loyalty-building aspects were assessed using the questionnaire established through an exploratory study. The data were analyzed with SPSS 22.0with the aid of Microsoft excel. Results: Nine out of ten variables were favorably connected with creating a loyal relationship with pharmaceutical retailers, according to the findings of the study. Limitations: This study focused only on Dhaka and Cumilla cities of Bangladesh. Contribution: The conclusion of the study is crucial and the outcome will have a long-term impact on how pharmaceutical companies use various types of tactics in loyalty-building programs with retailers.